BLACK SOLDIER MAGGOT AS PROTEIN ALTERNATIVE FISH FEED IN PRODUCING A GOOD PERFORMANCE OF Clarias sp. - giry marhento; Mashudi Alamsyah (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2021)
Black soldier maggot (Hermetia sp.) has a good prospective as protein alternative fish feed. The purpose of this study was to determine the effect of feeding Black soldier fly maggot on Clarias sp cultivation. The method used in this research was an experimental method with hypothesis testing using a randomized block design. It consisted of two treatments and 5 replications. Moreover, the parameter observed in this study were the length of Clarias sp. and weight of Clarias sp. Based on the research hypothesis testing using one-way ANOVA calculation, the length of Clarias sp. obtained f count 53.4, weight Clarias sp . It was obtained f count 3576.04, while f table 3.88. It states that, f count more than f table on length and weight of Clarias sp. Based on the average analysis, it is found that giving Black soldier fly maggot feed gives the best results because it has the highest average results.